Efektivitas Pelaporan Pajak Di Indonesia - Aulia Al Qori Hadistiyah; Rio Johan Putra (Owner : Riset dan Jurnal Akuntansi, 2022)
The current development strategy should be more directed at an independent Indonesian economy. This independence also includes independence in financing development. By doing this research, it is expected to be able to measure a country's success in optimizing tax funds' distribution fairly and equitably and to find out how much influence these variables have on taxpayers' perceptions of the ethics of tax avoidance. The urgency of this study is to examine the effect of tax amnesty, the self-assessment system, and the use of ESPT in tax reporting moderated by tax law enforcement on tax avoidance behavior. The method used is descriptive quantitative, the data analysis technique used in this research is a descriptive statistical test, classical assumption test, multiple regression test, and hypothesis testing. Judging from the statistical results of the T-test, it can be concluded that Tax amnesty and Self Assessment didn’t affect tax avoidance. However, ESPT and Law are proven to have a significant effect on tax avoidance. With the use of ESPT in tax reporting as well as law enforcement actually resulted in the occurrence of tax avoidance. This is indicated by taxpayers feeling they have a choice whether to report their taxes or not. And as for the applicable laws, not all of them are applied and there are gaps in their implementation so as to provide opportunities for taxpayers to carry out tax avoidance.